Degradation of 3D-Printed Porous Polylactic Acid Scaffolds Under Mechanical Stimulus - Chen, Heming; Shi, Quan; Shui, Hengtao; Wang, Peng; Chen, Qiang; Li, Zhiyong (Frontiers in Bioengineering and Biotechnology, 2021)
Polylactic acid (PLA) is a commonly used biodegradable polymer as scaffold material to repair tissue defects, and its degradation is associated with mechanical stimulus. In this study, the effect of mechanical stimulus on the degradation of 3D-printed PLA scaffolds was investigated by in vitro experiments and an author-developed numerical model. Forty-five samples with porosity 64.8% were printed to carry out the degradation experiment within 90 days. Statistical analyses of the mass, volume fraction, Young’s modulus and number average molecular weight, were made, and the in vitro experiments were further used to verify the proposed numerical model of the scaffold degradation. The results indicated that the mechanical stimulus could accelerate the degradation of the PLA scaffold, and the higher mechanical stimulus led to a faster degradation of the scaffolds at the late stage of the degradation process. In addition, the Young’s modulus and the number average molecular weight of the PLA scaffolds between the experiments and the numerical simulations were comparable, especially for the number average molecular weight. The present work could be helpful in the design of the biodegradable PLA scaffolds.